The Use of Multiple Intelligence Approach in Teaching English for Homeschooling Students Through Meaningful Activities: A Case Study At a Homeschooling in Banjar - Rika Ramadha Fashya (Journal of English Education Program (JEEP), 2023)
This study reported the implementation and perceptions of EFL homeschooling students in activating the Multiple Intelligences strategy through meaningful activities. This study employed qualitative case study at one of the Homeschoolings in Banjar. The data collection included observation and interview. The sampling was selected purposively. They were two homeschooling students in Banjar. The results of this study showed that multiple intelligences approach through meaningful activities resulted in a positive and good response. Students had different bits of intelligence and they could build their multiple intelligences through meaningful activities. The researcher recommends future researchers, who intend the research about the effect of multiple intelligence approaches and the use of meaningful activities to optimize student intelligence, invite more participants such as students in formal schools that always have more students.